Sexuality, race and empire in Alan Hollinghurst's "A Thieving Boy" (1983) - Dodson, E (Taylor and Francis, 2016)
By returning to the very start of Alan Hollinghurst’s literary career, this article begins constructing a different narrative about this “gay” British author -- one in which sexuality, race, and empire are intimately connected, and in which sexual liberation is haunted by imperial histories of racial exploitation. Through a “contrapuntal” analysis of his 1983 Egyptian short story “A Thieving Boy”, the article complicates dominant “queer” interpretations which overlook the postimperial politics – the aesthetic negotiation of Britain after empire – at stake in his representations of race and nation. In particular, through a dialogue with Hollinghurst’s non-fiction, it interrogates the political ambiguity of the story’s postimperial rewriting of E.M. Forster’s (homo)sexual awakening. It concludes by exploring the implications of this rereading for conventional conceptions of “postcolonial” and “British” contemporary fiction.